2016
DOI: 10.1111/fwb.12714
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the biological recovery of the Bohemian Forest lakes from acid stress

Abstract: Summary The response of planktonic (phytoplankton, ciliates, rotifers and crustaceans) and littoral (Ephemeroptera, Plecoptera, Trichoptera and Heteroptera: Nepomorpha) assemblages to chemical recovery was studied over a twelve‐year period (1999–2011) in eight glacial lakes in the Bohemian Forest (central Europe). The region suffered from high atmospheric pollution from the 1950s to the late 1980s, but has since been recovering from acidification due to 86% and 44% decrease in sulphur and nitrogen deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 75 publications
(152 reference statements)
0
30
0
Order By: Relevance
“…A much different situation has been found in Lake Ple sn e. This mountain lake suffered from a strong acidification due to the acid rains during the second half of the 20 th century. The drop in water pH caused the release of aluminum ions from the bedrock, resulting in the extiction of all the crustacean zooplankton species (Vrba et al, 2016). Nowadays, the lake contains high biomass of filamentous bacteria (Vrba et al, 2003) composed mostly of AAP bacteria (see Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A much different situation has been found in Lake Ple sn e. This mountain lake suffered from a strong acidification due to the acid rains during the second half of the 20 th century. The drop in water pH caused the release of aluminum ions from the bedrock, resulting in the extiction of all the crustacean zooplankton species (Vrba et al, 2016). Nowadays, the lake contains high biomass of filamentous bacteria (Vrba et al, 2003) composed mostly of AAP bacteria (see Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13°51'55” E) at an altitude of 1090 m a.s.l. The lake was heavily impacted by acid rains between the 1960's until the 1980's, which led to a strong acidification with water pH values of 4.0‐4.8 and the complete extinction of any crustacean zooplankton as well as fish (Vrba et al, ). The absence of these grazers resulted in its mesotrophic character with a relatively high standing stock of phytoplankton and unusual filamentous bacteria (Vrba et al, 2003) leading to a low water transparency (Secchi depth ∼ 1 m).…”
Section: Methodsmentioning
confidence: 99%
“…Acidification is a problem most often reported from rivers and lakes in Northern Europe, especially Scandinavian countries, UK and Ireland ( Aherne and Curtis, 2003 ; Posch et al, 2019 ). However, a recent study has shown that acidified surface waters may occur particularly in the following regions ( Austnes et al, 2018 ): the Pyrenees, border regions of Belgium, Luxembourg, France and Germany, mountainous regions on the borders of the Czech Republic (see Oulehle et al, 2017 ), Germany and Austria (see Vrba et al, 2016 ), the Tatra Mountains, the Italian Alps and northern Croatia.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we do not expect dramatic changes in lake water acidity after the decreased leaching of NO 3 − and P during forest regeneration. In contrast, a slow increase in water pH and ANC can be expected due to continuing ecosystem recovery from acidification (Oulehle et al ), similarly to other less acidified lakes in the same region (Vrba et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This situation differs from that in Rachelsee (another acidified lake in the same mountain area) where zooplankton recovery remarkably accelerated after tree dieback in its catchment (Vrba et al ). In Plešné Lake, two invertebrate predators, the introduced C. abyssorum together with original acid‐tolerant Heterocope saliens , reduced the rotifer abundance by three orders of magnitude until 2011 (Vrba et al ). More recent data, however, suggests an increase in rotifer abundance (Šorf M., pers.…”
Section: Discussionmentioning
confidence: 99%